Energy-saving and environment-friendly phase change CO2 trapping absorbent
By using a mixed solution of hydroxyethylethylenediamine, N-N diethylhydroxylamine and solvent, and adding iron oxide nanoparticles as reinforcement, the existing phase change CO2 capture absorber has solved the problems of small absorption capacity, low desorption efficiency and high regeneration energy consumption, and achieved an efficient and energy-saving CO2 capture effect.
Patent Information
- Application Number
- CN202411924321.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-12-25
AI Technical Summary
The existing phase-change CO2 capture absorbents have problems such as small absorption capacity, low desorption efficiency, unstable phase separation and high regeneration energy consumption, which limits their application in coal-fired power plants.
A mixed liquid composed of hydroxyethylethylenediamine, N-N diethylhydroxylamine and solvent is used as the phase change CO2 capture absorber, and a nanoparticle reinforcer iron oxide is added to improve absorption and desorption performance.
It significantly improves the absorption capacity and capture rate of CO2, reduces regeneration energy consumption, improves desorption efficiency, and enhances the stability of phase separation, achieving the energy-saving and environmentally friendly treatment requirements for CO2 capture.
Smart Images

Figure CN119733346A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of carbon dioxide capture absorbents, and in particular to an energy-saving and environment-friendly phase-change CO2 capture absorbent. Background Art
[0002] The combustion of fossil energy leads to large amounts of carbon dioxide emissions. Controlling CO2 emissions is the most feasible measure to mitigate global warming. Carbon capture, utilization and storage (CCUS) technology is one of the effective strategies to significantly reduce CO2 emissions. In view of the large amount of carbon emissions and the difficulty in capturing carbon dioxide from coal-fired power plants, compared with other technologies such as physical adsorption and membrane absorption, chemical absorption is a more complete and most widely used post-combustion capture route in industry. The chemical absorbents it uses are mostly relatively mature organic amine solvent systems. However, the traditional organic amine method also has the disadvantage of excessive energy consumption, of which regeneration energy consumption accounts for more than 60%, and excessive energy consumption has greatly restricted its development.
[0003] Existing research has shifted from single or multi-composite amine absorbents to phase change absorbents (two-phase absorbents), low-water absorbents and ionic liquids. Due to the high viscosity of ionic liquids, high energy consumption and high cost, it is difficult to industrialize them for the time being. Therefore, the absorption of carbon dioxide to form two incompatible phase change solvents has aroused more and more interest. Compared with traditional chemical absorbents, phase change solvent systems represent a class of materials that are expected to significantly reduce regeneration energy consumption. Compared with non-phase change processes, only the rich phase needs to be regenerated, so the energy consumption demand is significantly reduced.
[0004] Phase change absorbents can be divided into two phase change modes: phase change stratification after absorption and phase change stratification after regeneration. However, the research focus is mainly on the absorption system in which phase change stratification occurs after absorption. Liquid-liquid phase change absorbents are usually composed of amines, organic solvents, and water. According to the solution system, they can be divided into unit phase change absorbents, multi-component mixed absorbents, and anhydrous absorbents. However, existing phase change absorbents still generally have the disadvantages of small absorption capacity, low desorption efficiency, unstable phase separation, and high regeneration energy consumption. Therefore, in view of the above technical problems, it is necessary to provide an energy-saving and environmentally friendly phase change CO2 capture absorbent. Summary of the invention
[0005] The purpose of the present invention is to provide an energy-saving and environmentally friendly phase-change CO2 capture absorbent, which has the characteristics of large absorption capacity, high desorption efficiency, stable phase separation and low regeneration energy consumption.
[0006] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention is:
[0007] An energy-saving and environment-friendly phase-change CO2 capture absorbent is a mixed liquid prepared by configuring the following components in percentage by mass: 20%-30% hydroxyethylethylenediamine, 20-30% NN diethylhydroxylamine, and 50-60% solvent.
[0008] Furthermore, the absorbent also includes nanoparticle reinforcing agent iron oxide.
[0009] Preferably, the amount of the nanoparticle reinforcing agent iron oxide added is 1.5%-2.0% of the mass of the mixed solution.
[0010] Preferably, the absorbent is a mixed liquid prepared by configuring the following components in percentage by mass: 20% hydroxyethylethylenediamine, 30% NN diethylhydroxylamine, and 50% solvent; the absorbent also includes nanoparticle strengthener iron oxide, and the amount of nanoparticle strengthener iron oxide added is 2.0% of the mass of the mixed liquid.
[0011] Preferably, the solvent is one of sulfolane, n-propanol, diethylene glycol dimethyl ether and dimethyl sulfoxide.
[0012] Compared with the prior art, the present invention has the following beneficial effects:
[0013] The CO2 capture absorbent in the present invention can increase the absorption capacity of CO2 and improve the capture rate of CO2, while also reducing the regeneration energy consumption and improving the desorption effect, thereby achieving the energy-saving and environmentally friendly treatment requirements of CO2 capture. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 The effect diagrams of the absorption load and absorption time of the absorbents prepared in the embodiments of the present invention are shown respectively;
[0015] Figure 2 The effect diagrams of the absorption rate and absorption time of the absorbents prepared in the embodiments of the present invention are shown respectively;
[0016] Figure 3 The effect diagram of the desorption load and absorption time of the absorbent prepared in the examples of the present invention;
[0017] Figure 4 The effect diagrams of the desorption rate and absorption time of the absorbents prepared in the embodiments of the present invention are shown respectively;
[0018] Figure 5 The following are the layering effect diagrams of the absorbents prepared in the examples of the present invention. DETAILED DESCRIPTION
[0019] The present invention is further described in detail below in conjunction with specific embodiments.
[0020] Example 1
[0021] An energy-saving and environment-friendly phase-change CO2 capture absorbent is a mixed solution prepared by configuring the following components in percentage by mass: 20g of hydroxyethylethylenediamine (AEEA), 20g of NN diethylhydroxylamine (DEHA), and 60g of sulfolane.
[0022] Preparation method: AEEA and DEHA are weighed according to the ratio and added into a container, and then sulfolane is added, and the mixture is stirred evenly to obtain a phase change CO2 capture absorbent.
[0023] Process for testing the absorption performance of the absorbent: Place the container containing the absorbent of this embodiment in a 40°C constant temperature water bath and keep it warm to 40°C, then introduce high-purity carbon dioxide gas until the absorbent is saturated with absorption. During the absorption process, the absorption load of the phase change absorption solvent is recorded using the difference between the mass flowmeter and the wet flowmeter. By differentiating the relationship between the absorption load and time, the relationship between the absorption rate of the solution and time can be obtained. Place the absorbed rich phase in a 130°C oil bath for heating and desorption, and record the wet flowmeter value as the desorption load of the solvent. By differentiating the relationship between the desorption load and time, the relationship between the desorption rate of the solution and time can be obtained.
[0024] Result: After the absorbent is saturated, a liquid-liquid phase transition occurs. Figure 5 As shown in the figure, the upper liquid phase is the lean phase, and the lower liquid phase is the rich phase. The volume of the rich phase is 57mL, and the volume of the lean phase is 45mL. Figure 1 and Figure 2 As shown, after 40 minutes of absorption, the absorption amount of the absorbent is 0.81 molCO2 / mol, and the absorption rate is 4.82e -4 mol / mol / s; e.g. Figure 3 and Figure 4 As shown, the desorption amount of the absorbent is 0.63 molCO2 / mol, and the desorption rate is 2.9e -4 mol / mol / s.
[0025] Example 2
[0026] An energy-saving and environment-friendly phase-change CO2 capture absorbent is a mixed solution prepared by configuring the following components in percentage by mass: 20g of hydroxyethylethylenediamine (AEEA), 30g of NN diethylhydroxylamine (DEHA), and 50g of cyclopentane sulfone; the absorbent also includes 1.6g of nanoparticle enhancer iron oxide.
[0027] Preparation method: AEEA, DEHA and nano-particle enhancer iron oxide are weighed according to the ratio and added into a container, and then sulfolane is added, and the mixture is mixed and stirred evenly to obtain a phase change CO2 capture absorbent.
[0028] The process of detecting the absorption and desorption performance of the absorbent remains consistent with that of Example 1.
[0029] Result: After the absorbent is saturated, a liquid-liquid phase transition occurs. Figure 5 As shown in the figure, the upper liquid phase is the lean phase, and the lower liquid phase is the rich phase. The volume of the rich phase is 56mL, and the volume of the lean phase is 46mL. Figure 1 and Figure 2 As shown, after 40 minutes of absorption, the absorption amount of the absorbent is 0.93 molCO2 / mol, and the absorption rate is 4.92e -4 mol / mol / s; e.g. Figure 3 and Figure 4 As shown, the desorption amount of the absorbent is 0.69 molCO2 / mol, and the desorption rate is 3.19e -4 mol / mol / s.
[0030] Example 3
[0031] An energy-saving and environment-friendly phase-change CO2 capture absorbent is a mixed solution prepared by configuring the following components in percentage by mass: 20g hydroxyethylethylenediamine (AEEA), 20g NN diethylhydroxylamine (DEHA), and 60g n-propanol; the absorbent also includes 1.9g of nanoparticle enhancer iron oxide.
[0032] The preparation method and the process of detecting the absorption and desorption performance of the absorbent are consistent with those in Example 1.
[0033] Result: After the absorbent is saturated, a liquid-liquid phase transition occurs. Figure 5 As shown in the figure, the upper liquid phase is the lean phase, and the lower liquid phase is the rich phase. The volume of the rich phase is 57mL, and the volume of the lean phase is 45mL. Figure 1 and Figure 2 As shown, after 40 minutes of absorption, the absorption amount of the absorbent is 0.97 molCO2 / mol, and the absorption rate is 4.93e -4 mol / mol / s; e.g. Figure 3 and Figure 4 As shown, the desorption amount of the absorbent is 0.71 molCO2 / mol, and the desorption rate is 3.29e -4 mol / mol / s.
[0034] Example 4
[0035] An energy-saving and environment-friendly phase-change CO2 capture absorbent is a mixed solution prepared by configuring the following components in percentage by mass: 20g of hydroxyethylethylenediamine (AEEA), 30g of NN diethylhydroxylamine (DEHA), and 50g of n-propanol; the absorbent also includes 2.0g of nanoparticle enhancer iron oxide.
[0036] The preparation method and the process of detecting the absorption and desorption performance of the absorbent are consistent with those in Example 1.
[0037] Result: After the absorbent is saturated, a liquid-liquid phase transition occurs. Figure 5 As shown in the figure, the upper liquid phase is the lean phase, and the lower liquid phase is the rich phase. The volume of the rich phase is 56mL, and the volume of the lean phase is 46mL. Figure 1 and Figure 2 As shown, after 40 minutes of absorption, the absorption amount of the absorbent is 1.03 molCO2 / mol, and the absorption rate is 4.91e -4 mol / mol / s; e.g. Figure 3 and Figure 4 As shown, the desorption amount of the absorbent is 0.72 molCO2 / mol, and the desorption rate is 3.09e -4 mol / mol / s.
[0038] Example 5
[0039] An energy-saving and environment-friendly phase-change CO2 capture absorbent is a mixed solution prepared by configuring the following components in percentage by mass: 20g of hydroxyethylethylenediamine (AEEA), 20g of NN diethylhydroxylamine (DEHA), and 60g of diethylene glycol dimethyl ether; the absorbent also includes 1.5g of nanoparticle enhancer iron oxide.
[0040] The preparation method and the process of detecting the absorption and desorption performance of the absorbent are consistent with those in Example 1.
[0041] Result: After the absorbent is saturated, a liquid-liquid phase transition occurs. Figure 5 As shown in the figure, the upper liquid phase is the lean phase, and the lower liquid phase is the rich phase. The volume of the rich phase is 59 mL, and the volume of the lean phase is 43 mL. Figure 1 and Figure 2 As shown, after 40 minutes of absorption, the absorption amount of the absorbent was 1.04 molCO2 / mol, and the absorption rate was 4.92e -4 mol / mol / s; e.g. Figure 3 and Figure 4 As shown, the desorption amount of the absorbent is 0.73 molCO2 / mol, and the desorption rate is 3.29e -4 mol / mol / s.
[0042] Example 6
[0043] An energy-saving and environment-friendly phase-change CO2 capture absorbent is a mixed solution prepared by configuring the following components in percentage by mass: 20g hydroxyethylethylenediamine (AEEA), 30g NN diethylhydroxylamine (DEHA), 50g diethylene glycol dimethyl ether; the absorbent also includes 1.7g of nanoparticle enhancer iron oxide.
[0044] The preparation method and the process of detecting the absorption and desorption performance of the absorbent are consistent with those in Example 1.
[0045] Result: After the absorbent is saturated, a liquid-liquid phase transition occurs. Figure 5 As shown in the figure, the upper liquid phase is the lean phase, and the lower liquid phase is the rich phase. The volume of the rich phase is 60mL, and the volume of the lean phase is 42mL. Figure 1 and Figure 2 As shown, after 40 minutes of absorption, the absorption amount of the absorbent is 1.04 molCO2 / mol, and the absorption rate is 4.82e -4 mol / mol / s; e.g. Figure 3 and Figure 4 As shown, the desorption amount of the absorbent is 0.77 molCO2 / mol, and the desorption rate is 3.39e -4 mol / mol / s.
[0046] Example 7
[0047] An energy-saving and environment-friendly phase-change CO2 capture absorbent is a mixed solution prepared by configuring the following components in percentage by mass: 20g hydroxyethylethylenediamine (AEEA), 20g NN diethylhydroxylamine (DEHA), 60g dimethyl sulfoxide; the absorbent also includes 1.9g of nanoparticle enhancer iron oxide.
[0048] The preparation method and the process of detecting the absorption and desorption performance of the absorbent are consistent with those in Example 1.
[0049] Result: After the absorbent is saturated, a liquid-liquid phase transition occurs. Figure 5 As shown in the figure, the upper liquid phase is the lean phase, and the lower liquid phase is the rich phase. The volume of the rich phase is 59 mL, and the volume of the lean phase is 43 mL. Figure 1 and Figure 2 As shown, after 40 minutes of absorption, the absorption amount of the absorbent is 1.08 molCO2 / mol, and the absorption rate is 4.42e -4 mol / mol / s; e.g. Figure 3 and Figure 4 As shown, the desorption amount of the absorbent is 0.82 molCO2 / mol, and the desorption rate is 3.17e -4 mol / mol / s.
[0050] Example 8
[0051] An energy-saving and environment-friendly phase-change CO2 capture absorbent is a mixed solution prepared by configuring the following components in percentage by mass: 20g hydroxyethylethylenediamine (AEEA), 30g NN diethylhydroxylamine (DEHA), 50g dimethyl sulfoxide; the absorbent also includes 2.0g of nanoparticle enhancer iron oxide.
[0052] The preparation method and the process of detecting the absorption and desorption performance of the absorbent are consistent with those in Example 1.
[0053] Result: After the absorbent is saturated, a liquid-liquid phase transition occurs. Figure 5 As shown in the figure, the upper liquid phase is the lean phase, and the lower liquid phase is the rich phase. The volume of the rich phase is 60mL, and the volume of the lean phase is 42mL. Figure 1 and Figure 2 As shown, after 40 minutes of absorption, the absorption amount of the absorbent is 1.28 molCO2 / mol, and the absorption rate is 4.32e -4 mol / mol / s; e.g. Figure 3 and Figure 4 As shown, the desorption amount of the absorbent is 0.85 molCO2 / mol, and the desorption rate is 3.21e -4 mol / mol / s.
[0054] The phase-change absorbents for capturing carbon dioxide provided in Examples 1 to 8 all exhibit phase separation after absorbing carbon dioxide. The absorption load, desorption load and phase separation volume are shown in the following table.
[0055]
[0056] Among them, the phase change absorbent for capturing carbon dioxide provided in Example 8 (i.e., the content of AEEA and DEHA accounts for 50% of the total mass), the maximum CO2 loading amount when the nanoparticles are 2.0g is: 1.28molCO2 / mol; the phase change absorbent for capturing carbon dioxide provided in Example 1 (i.e., the content of AEEA and DEHA accounts for 40% of the total mass), the minimum CO2 loading amount is: 0.81molCO2 / mol.
[0057] In summary, according to the above experimental results, the absorbent content and the amount of nanoparticles added have a certain influence on CO2 absorption. Among them, the CO2 absorbent made of a mixed solution prepared by 20% by mass of hydroxyethylethylenediamine, 30% by mass of NN diethylhydroxylamine, and 50% by mass of solvent, and the addition amount of nanoparticle enhancer iron oxide is 2.0% by mass of the mixed solution has the best effect.
Claims
1. An energy-saving and environmentally friendly phase-change CO2 capture absorbent, characterized in that: The mixed solution is prepared by configuring the following components in percentage by mass: 20%-30% of hydroxyethylethylenediamine, 20%-30% of NN diethylhydroxylamine, and 50%-60% of solvent.
2. The energy-saving and environmentally friendly phase-change CO2 capture absorbent according to claim 1, characterized in that: Also included is a nanoparticle strengthener, iron oxide.
3. The energy-saving and environmentally friendly phase-change CO2 capture absorbent according to claim 2, characterized in that: The amount of the nano-particle reinforcing agent iron oxide added is 1.5%-2.0% of the mass of the mixed solution.
4. The energy-saving and environmentally friendly phase-change CO2 capture absorbent according to claim 3, characterized in that: The mixed liquid is prepared by configuring the following components in percentage by mass: 20% hydroxyethylethylenediamine, 30% NN diethylhydroxylamine, and 50% solvent; the absorbent also includes nanoparticle reinforcing agent iron oxide, and the amount of the nanoparticle reinforcing agent iron oxide added is 2.0% of the mass of the mixed liquid.
5. An energy-saving and environmentally friendly phase-change CO2 capture absorbent according to claim 1 or 2, characterized in that: The solvent is one of sulfolane, n-propanol, diethylene glycol dimethyl ether and dimethyl sulfoxide.
Citation Information
Patent Citations
Novel amine solvent blends
CN106663491A
Alkali-metal-based nano fluid CO2 absorption solution
CN107261762A
Thermophotovoltaic electrical power generator
CN109247031A
Non-aqueous liquid-liquid phase-change absorbent for capturing carbon dioxide and application of non-aqueous liquid-liquid phase-change absorbent
CN112107966A
Process for removing CO2 and / or H2S from a gas comprising CO2 and / or H2S
EP2283911A1